The Effect of Canva App-Assisted Interactive Learning Media on Elementary School Grade IV Math Learning Interest - Miftakul Nur Wahyu Ning Tias; Dya Ayu Agustiana Putri; Eka Yuliana Sari (Theta: Journal of Statistics, 2026)
This study aims to examine the influence of interactive learning media assisted by the Canva application on the interest in learning mathematics in grade IV in elementary school. This study is a type of quantitative research using Quasi-Experimental Design with Nonequivalent Control Group Design. Data were obtained from 53 students who were divided into an experimental group (who participated in the interactive learning media assisted by the Canva app) and a control group (who did not participate in the interactive learning media assisted by the Canva application). The instrument used is a learning interest questionnaire with validity and reliability that has been tested using the JAMOVI 2.7.12 application. The analysis showed that the instrument had high reliability with a Cronbach's Alpha coefficient of 0.974 and adequate validity. Based on the results of the statistical test, there was a significant increase in student learning interest in the experimental group compared to the control group after the implementation of interactive learning media assisted by the Canva application (p< 0.001). These results show that interactive learning media assisted by the Canva application has a positive influence on increasing interest in learning mathematics. This research supports the importance of the application of interactive learning media in elementary schools to increase students' interest in learning mathematics.